Analisis rasio solvabilitas untuk menilai kinerja keuangan terhadap aset dan equity pada pt. Adaro energy indonesia tbk. Periode 2020-2024 - Fauzi, Moh. (Maliki Interdisciplinary Journal, 2025)
This research analyzes the solvency ratio of PT. Adaro Energy Tbk for the 2020–2024 period, focusing on the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) to evaluate the company's ability to fulfill its financial obligations. The results of the analysis show that DER has fluctuated, increasing from 61% in 2020 to 70% in 2021, then decreasing to 34% in 2024. A similar trend can be seen in DAR, which decreased from 38% in 2020 to 25% in 2024. This decrease reflects the decrease the company's reliance on debt, indicating increased financial stability and better risk management. These findings provide insight for stakeholders for decision making regarding investment and financial strategies.